Sonochemical Synthesis of Er3+-Doped ZnO Nanospheres with Enhanced Upconversion Photoluminescence. (18th October 2012) - Geng, Jun; Song, Guang-Hui; Zhu, Jun-Jie
Abstract : Er 3+ -doped ZnO nanospheres have been synthesized via a sonochemical conversion process. The formation mechanism of these nanocrystals is connected with the sonochemical effect of ultrasound irradiation. The as-preparedEr 3+ doped ZnO nanospheres show enhanced photoluminescence and upconversion photoluminescence properties compared with pure ZnO.